Cover Feature: Ordered Mesoporous CeO2‐supported Ag as an Effective Catalyst for Carboxylative Coupling Reaction Using CO2 (ChemCatChem 8/2019). Issue 8 (8th April 2019) - Zhang, Xiao; Wang, Dingkun; Jing, Meizan; Liu, Jian; Zhao, Zhen; Xu, Guanhua; Song, Weiyu; Wei, Yuechang; Sun, Yuanqing
Abstract : The Cover Feature shows that Ag/Mesoporous CeO2 could be used in the carboxylative coupling of terminal alkynes, chloride compounds and CO2 . In their Full Paper, X. Zhang et al. demonstrate that Ag/M‐CeO2 catalysts synthesized through the gas bubbling‐assisted membrane reduction (GBMR) method contain uniform mesoporous structure, large surface area and oxygen vacancies, which promote the dispersion of Ag nanoparticles. Density functional theory (DFT) calculations indicate that Ag nanoparticles supported on M‐CeO2 could facilitate the formation of oxygen vacancies, which result in higher CO2 adsorption capacity. A wide range of functionalized 2‐alkynoates could be synthesized by Ag(3.12%)/M‐CeO2 catalyst in good yield. More information can be found in the Full Paper by X. Zhang et al. onpage 2089 in Issue 8, 2019 (DOI:10.1002/cctc.201900039 ).